2013
DOI: 10.1089/scd.2012.0168
|View full text |Cite
|
Sign up to set email alerts
|

Lengthened G1 Phase Indicates Differentiation Status in Human Embryonic Stem Cells

Abstract: Human embryonic stem cells (hESC) have potential applications as tools for drug screening to identify small molecule regulators of self-renewal or differentiation. Elucidating the mechanisms governing lineage commitment in hESC will allow for efficient derivation of specified cell types for clinical use. Recognizing the early steps in loss of pluripotency is key to achieving both goals of drug screening and derivation of therapeutically relevant cell types. Here we report the use of a real time cell cycle fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
124
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 72 publications
11
124
0
Order By: Relevance
“…We show here that EndoC-βH2 Fucci derivatives should give additional grips to further experimentally assess these events. In some stem cells/progenitors, such as mouse neural stem cells/progenitors or human embryonic stem cells, an increasing intensity of the orange Fucci indicator reflects ongoing differentiation most probably because both events are linked to G1 lengthening [2], [37], [38]. In the same way, FACS sorting experiments revealed that the mRNA levels of two markers of mature beta cells, INSULIN and IAPP , are higher in the brightest orange Cre-transduced EndoC-βH2 Fucci sub-population than in other orange Cre-transduced cells and, to a much greater extent, than in control (Zeo-transduced) orange cells.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that EndoC-βH2 Fucci derivatives should give additional grips to further experimentally assess these events. In some stem cells/progenitors, such as mouse neural stem cells/progenitors or human embryonic stem cells, an increasing intensity of the orange Fucci indicator reflects ongoing differentiation most probably because both events are linked to G1 lengthening [2], [37], [38]. In the same way, FACS sorting experiments revealed that the mRNA levels of two markers of mature beta cells, INSULIN and IAPP , are higher in the brightest orange Cre-transduced EndoC-βH2 Fucci sub-population than in other orange Cre-transduced cells and, to a much greater extent, than in control (Zeo-transduced) orange cells.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these mechanisms has been demonstrated in adult stem cells (Oshimori and Fuchs 2012) and also in pluripotent stem cells (Sela et al 2012;Calder et al 2013;Coronado et al 2013;Singh et al 2013Singh et al , 2015. Human embryonic stem cells (hESCs) represent an advantageous model system for investigating the cross-talk between cell cycle and cell fate choice.…”
mentioning
confidence: 99%
“…The likely importance of this altered cell cycle structure for maintaining pluripotency is underscored by evidence that pluripotent cells 12 and ESCs lose this unusual profile upon differentiation, [13][14][15][16] and, conversely, that somatic cells regain it when reprogrammed. 17,18 We recently used a biophysical separation method to fractionate mouse ESCs according to size and cell cycle stage.…”
mentioning
confidence: 99%